Prevalence of Rumen and Reticulum Trematodes in The Goat Slaughtered at Pegirian Surabaya Slaughter House using Digestive Surgery Method - Novia Intan Kurnia; Setiawan Koesdarto; Herry Agoes Hermadi; Kusnoto Kusnoto; Hardany Primarizky; Agus Sunarso (Journal of Parasite Science (JoPS), 2019)
The purpose of this study was to determine the kind of trematodes which infected the rumen and reticulum of goat slaughtered at RPH Pegirian Surabaya using digestive surgery method, and determine the prevalence result. 36 samples of rumen and reticulum were collected from RPH Pegirian from September - November 2017 then using digestive surgery to obtain fresh adult worms, afterwards using the Semichen-Acetic Carmine staining method to makes the object easy to identifying. The results showed that species was found on goat was Paramphistomum cervi and Cotylophoron cotylophorum, in the Paramphistomum cervi are several characters wich is oral sucker, genital pore, uterus, testis, ventral sucker and in Cotylophoron cotylophorum contain oral sucker, branched oesophagus, uterus, vitelin glands, testes , posterior sucker. 3 rumen positive trematodosis with prevalence of 8.33% Chi-square statistic test (p>0.05) showed no effect between goat species and Trematodosis prevalence, 20 kacang goat and 16 peranakan etawa goat found 2 positive kacang goat (10%) and 1 peranakan etawa goat positive (6.25%).